Slot‐Die‐Coated Organic Solar Cells Optimized through Multistep Crystallization Kinetics. Issue 6 (2nd February 2022) - Xu, Jinqiu; Zhan, Junzhe; Zhou, Guanqing; Zhong, Wenkai; Zhang, Ming; Xue, Xiaonan; Zhu, Lei; Leng, Shifeng; Chen, Jiajun; Zou, Yecheng; Su, Xuan; Shi, Zhiwen; et al.
Abstract : To fabricate organic solar cells (OSCs) via slot‐die coating, solvent additives are essential to induce an optimized phase‐separated and order morphology. It is critical to determine the morphological evolution from solution to solid state and understand the crystallization kinetics in slot‐die coating. Using in situ grazing‐incidence wide‐angle X‐ray scattering characterization, the morphological evolution in PM6‐ and ITIC‐based systems without or with 0.3% 1, 8‐diiodooctane (DIO) as additive can be monitored in real‐time during slot‐die coating. As a result, DIO weakens the planarization of the PM6 backbone and splits the backbone ordering into fragments to form ordered crystallites. DIO also induces surface crystallization to reinforce the tie‐chain connections between the crystallites. Furthermore, in the ITIC system, DIO triggers the formation of an interconnected fibril network morphology and concurrently promotes the stacking of ITIC molecules in between the polymer network. Thus, an optimized morphology with a refined crystal structure is formed with the help of DIO. As a result, the power conversion efficiency is improved from 8.77% to 9.59% in slot‐die‐coated OSCs. These findings provide guidelines for optimizing the morphology in slot‐die‐coated OSCs and accelerate the transition of laboratory‐scale fabrication to industrial production. Abstract : In PM6:ITIC blend films, 1, 8‐diiodooctane (DIO) weakens the planarization of the PM6 backbone and splits the backbone ordering into fragments. Meanwhile, DIO also promotes the packing of ITIC molecules and their uniform deposition in between the polymer network. Such morphology optimization gives rise to a better performance of solar cells.